2017
DOI: 10.1002/prp2.283
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diazepam administration increases the expression of Lcn2 in the CNS

Abstract: Benzodiazepines (BZDs), which bind with high affinity to gamma‐aminobutyric acid type A receptors (GABAA‐Rs) and potentiate the effects of GABA, are widely prescribed for anxiety, insomnia, epileptic discharge, and as anticonvulsants. The long‐term use of BZDs is limited due to adverse effects such as tolerance, dependence, withdrawal effects, and impairments in cognition and learning. Additionally, clinical reports have shown that chronic BZD treatment increases the risk of Alzheimer's disease. Unusual GABAA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…Studies have also revealed cellular changes after diazepam treatment. 14,55 On the other hand, low dose gamma radiation or resveratrol treatments prior to diazepam treated mice showed a noticeable enhancement in the overall histo-architecture of brain areas, which may be accredited to their neuroprotective role in reducing the levels of free radicals and regulating the activities of antioxidant enzymes thereby preventing cellular damage. 14 Besides, brain sections of LDR and resveratrol treatment group showed the same histological picture of control normal group and improvement than diazepam group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also revealed cellular changes after diazepam treatment. 14,55 On the other hand, low dose gamma radiation or resveratrol treatments prior to diazepam treated mice showed a noticeable enhancement in the overall histo-architecture of brain areas, which may be accredited to their neuroprotective role in reducing the levels of free radicals and regulating the activities of antioxidant enzymes thereby preventing cellular damage. 14 Besides, brain sections of LDR and resveratrol treatment group showed the same histological picture of control normal group and improvement than diazepam group.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining: The OSW and MCA samples were permeabilized with 0.025% Triton X-100 (Fisher Scientific, #BP151-100), and blocked with freshly prepared 10% Donkey serum with 1% Bovine Serum Albumin (Gemini Bio-Products, #700-100P) for 2 hours. After blocking, the following primary antibodies were applied, and left overnight at 4˚C: mouse monoclonal anti-human neutrophil elastase (NE) (1:100, Dako, Clone NP57, #M0752); 56,57 rabbit polyclonal to histone H3 (1:100, citrulline R2+R8+R17, 1:100, Abcam, #ab5103); 58,59 rabbit polyclonal Keratin-14 (1:1000, BioLegend, #905301, Covance #PRB-155P); 60,61 rabbit polyclonal anti-human Myeloperoxidase (MPO) (1:100, Abcam, #ab45977); 62,63 rabbit monoclonal anti-human CD3 (1:100, Abcam, #ab16669); 64,65 rabbit polyclonal anti-Oncostatin M (LifeSpan Biosciences, #LS-C104796); rabbit polyclonal NGAL (1:100, Abcam, #ab63929); 66,67 and rabbit polyclonal LIGHT/TNFSF14 (1:100, LifeSpan Biosciences, #LS-C118682). Isotype controls were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Under physiological conditions in a murine model, the expression of LCN2 mRNA and LCN2 protein in the brain appears to be very low to absent . However, only a few studies have reported LCN2 protein expression in the hippocampus, cortex and amygdala of normal mice and the hippocampus of normal adult rats …”
Section: Lcn2 With Respect To Physiological Condition and Cognitionmentioning
confidence: 97%
“…LCN2 had no effect on cognitive function in basal condition 30 very low to absent. 6,8,11,[24][25][26] However, only a few studies have reported LCN2 protein expression in the hippocampus, 27,28 cortex and amygdala 28 of normal mice and the hippocampus of normal adult rats. 10 Several studies have shown no significant difference between the cognitive function of wild-type mice and LCN2 null mice (Table 1).…”
Section: ↔ Cognitionmentioning
confidence: 99%
See 1 more Smart Citation